Costs and outcomes of Lynch syndrome screening in the Australian colorectal cancer population. Issue 10 (17th May 2018) - Cenin, Dayna R; Naber, Steffie K; Lansdorp‐Vogelaar, Iris; Jenkins, Mark A; Buchanan, Daniel D; Preen, David B; Ee, Hooi C; O'Leary, Peter
Abstract: Background and Aim: Individuals with Lynch syndrome (LS) are at increased risk of LS‐related cancers including colorectal cancer (CRC). CRC tumor screening for mismatch repair (MMR) deficiency is recommended in Australia to identify LS, although its cost‐effectiveness has not been assessed. We aim to determine the cost‐effectiveness of screening individuals with CRC for LS at different age‐at‐diagnosis thresholds. Methods: We developed a decision analysis model to estimate yield and costs of LS screening. Age‐specific probabilities of LS diagnosis were based on Australian data. Two CRC tumor screening pathways were assessed (MMR immunohistochemistry followed by MLH1 methylation ( MLH1 ‐Pathway) or BRAF V600E testing ( BRAF ‐Pathway) if MLH1 expression was lost) for four age‐at‐diagnosis thresholds—screening < 50, screening < 60, screening < 70, and universal screening. Results: Per 1000 CRC cases, screening < 50 identified 5.2 LS cases and cost $A7041 per case detected in the MLH1 ‐Pathway. Screening < 60 increased detection by 1.5 cases for an incremental cost of $A25 177 per additional case detected. Screening < 70 detected 1.6 additional cases at an incremental cost of $A40 278 per additional case detected. Compared with screening < 70, universal screening detected no additional LS cases but cost $A158 724 extra. The BRAF ‐Pathway identified the same number of LS cases for higher costs. Conclusions: The MLH1 ‐Pathway is more cost‐effective than BRAF ‐Pathway for all age‐at‐diagnosis thresholds. MMR immunohistochemistry tumor screening in individuals diagnosed with CRC aged < 70 years resulted in higher LS case detection at a reasonable cost. Further research into the yield of LS screening in CRC patients ≥ 70 years is needed to determine if universal screening is justified.